PHYSIOTHERAPY THROUGH EXERGAMES – INFLUENCE IN THE DEVELOPMENT OF STATIC BALANCE FOR CHILDREN WITH NEUROMOTOR DISABILITIES - BAIAS, Maria-Sofia; SANDOR, Iosif; BOROS-BALINT, Iuliana (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
Objective: This study investigates the effectiveness of an innovative therapeutic protocol aimed at enhancing static balance of children with neuromotor disabilities. Exergames and proprioceptive neuromuscular facilitation methods are to be combined and applied as a physiotherapeutic technique to improve standard deviations of the center of pressure (CoP) in different planes and axes. Method and materials: The therapeutic program involved the application of proprioceptive neuromuscular facilitation techniques using repeated stimulation, performed concurrently with interactive exergaming tasks on the MIRA Rehab digital platform. Exercises were conducted on an unstable support surface (balance board) to stimulate postural adjustment. Quantitative measurements of postural control were collected using BTWalk software, focusing on CoP variability. Results: Comparative analysis of pre- and post-intervention data indicated a statistically significant reduction in the standard deviation values of CoP displacement in both the antero-posterior and medio-lateral directions. These findings support an improvement in static postural stability following the intervention. Discussion: Improvements observed are attributed to various factors: the engaging, gamified MIRA Rehab system boosted motivation; motor tasks across multiple planes enhanced neuromuscular activation; and a task-oriented approach facilitated sensorimotor learning through repetition and feedback. Although minor improvements in CoP control on a fixed surface were noted, they were not statistically significant, indicating that children with NMD might benefit more from dynamic stimuli that challenge balance and sensorimotor integration. These findings support previous research on the advantages of interactive virtual rehabilitation in pediatric neurorehabilitation, showing that exergames enhance balance control and improve therapy adherence. Conclusions: This study demonstrates that an exergame-based balance training program using the MIRA Rehab platform can produce statistically significant improvements in postural stability on unstable surfaces in children with neuromotor disabilities. The intervention was effective in reducing CoP displacement in both sagittal and frontal planes, indicating better control of the center of gravity during challenging postural tasks.